Global human resource management casebook - Hayton, James C. (Routledge global human resource management series, 2012)
"The Global Human Resource Management Casebook' is a collection of business teaching cases, focusing on Human Resource Management issues around the world. Each case is based in a single country and illustrates one or more significant challenge faced by managers and HR practitioners. The influence of the unique national cultural and institutional context upon the issues in the case is emphasized. In total 32 unique and original cases are presented, each from different national contexts. Every case is followed by a set of questions for use in class discussion or private study of the cases